2021
DOI: 10.1021/acs.inorgchem.1c02720
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Phase Transition Containing Switchable Dielectric Behavior, Long Fluorescence Lifetime, and Distinct Photoluminescence Changes in a 2D Hybrid CuBr4 Perovskite

Abstract: A novel organic–inorganic hybrid perovskite crystal, [ClC6H4(CH2)2NH3]2CuBr4 (1), having experienced an invertible high-temperature phase transition near T c (the Curie temperature T c = 355 K), has been successfully synthesized. The phase-transition characteristics for compound 1 are thoroughly revealed by specific heat capacity (C p), differential thermal analysis, and differential scanning calorimetry tests, possessing 16 K broad thermal hysteresis. Multiple-temperature powder X-ray diffraction analysis fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…10,11 Lin, Zhou et al reported low-dimensional OMHH exhibiting remarkable properties compared to 2D and 3D OMHHs, due to the strong quantum confinement and site isolation in 1D. 12 C 4 N 2 H 14 PbBr 4 display efficient bluish white-light emissions with photoluminescence quantum efficiencies of approximately 20%, due to its unique one-dimensional structure which enables strong quantum confinement with the formation of self-trapped excited states. 13 Ian C. Smith et al reported in his work that low-dimensional inorganic–organic hybrid materials tend to show better moisture resistance than multi-dimensional hybrid materials, which may benefit from the connection model of the inorganic component with the organic one.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Lin, Zhou et al reported low-dimensional OMHH exhibiting remarkable properties compared to 2D and 3D OMHHs, due to the strong quantum confinement and site isolation in 1D. 12 C 4 N 2 H 14 PbBr 4 display efficient bluish white-light emissions with photoluminescence quantum efficiencies of approximately 20%, due to its unique one-dimensional structure which enables strong quantum confinement with the formation of self-trapped excited states. 13 Ian C. Smith et al reported in his work that low-dimensional inorganic–organic hybrid materials tend to show better moisture resistance than multi-dimensional hybrid materials, which may benefit from the connection model of the inorganic component with the organic one.…”
Section: Introductionmentioning
confidence: 99%
“…Further calculation and analysis displayed that the PL lifetime of 1 is 43.998 μs, and is larger than that of numerous superior PL materials, e.g. , (γ-methoxy propyl amine) 2 PbBr 4 (2.52 ns), 43 CH 3 NH 3 PbI 3 (299.3 ns), 44 Cu 4 I 4 (dcpm) 2 (6.22 μs), 45 and slightly shorter than [ClC 6 H 4 (CH 2 ) 2 NH 3 ] 2 CuBr 4 (55.46 μs), 15 indicating that 1 possesses potential application in fluorescence devices.…”
Section: Resultsmentioning
confidence: 94%
“…1–7 Molecular phase-transition materials are principally divided into host–guest inclusion compounds, 8–10 anion–cation organic salts, 11,12 and perovskite/perovskite-like compounds. 13–15 Among them, the host–guest inclusions represented by organic ammonium–crown ether families are a class of greatly prospective ferroelectric–dielectric materials with potential applications in various fields, e.g. , switchable dielectric devices, sensors, digital processing, luminescence, molecular catalysis, molecular recognition and photoelectric technology, and have aroused growing research interest in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Among them, the behavior of dielectric response is one of the most intriguing features, because it could switch between a high-dielectric state and a low-dielectric state around the phase transition temperature. [11][12][13][14] At present, as a new branch of phase transition materials, organic-inorganic phase transition materials have received widespread research enthusiasm because of their simple synthesis and flexible structure. [15][16][17][18] Therefore, it provides a research direction for exploring new dielectric materials.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that many physical properties (such as dielectric, piezoelectricity and ferroelectricity) transition occur near the phase transition temperature [6–10] . Among them, the behavior of dielectric response is one of the most intriguing features, because it could switch between a high‐dielectric state and a low‐dielectric state around the phase transition temperature [11–14] . At present, as a new branch of phase transition materials, organic‐inorganic phase transition materials have received widespread research enthusiasm because of their simple synthesis and flexible structure [15–18] .…”
Section: Introductionmentioning
confidence: 99%